Charge separation relative to the reaction plane in Pb-Pb collisions at √sNN=2.76 TeV - Abelev, B.; Adam, J.; Adamova, D.; Adare, A. M.; Aggarwal, M. M.; Rinella, G. Aglieri; Agocs, A. G.; Agostinelli, A.; Salazar, S. Aguilar; Ahammed, Z.; Ahmad, N.; Masoodi, A. Ahmad; et al. (AMER PHYSICAL SOC, 2013)
Measurements of charge-dependent azimuthal correlations with the ALICE detector at the LHC are reported for Pb-Pb collisions at root s(NN) = 2.76 TeV. Two- and three-particle charge-dependent azimuthal correlations in the pseudorapidity range vertical bar eta vertical bar < 0.8 are presented as a function of the collision centrality, particle separation in pseudorapidity, and transverse momentum. A clear signal compatible with a charge-dependent separation relative to the reaction plane is observed, which shows little or no collision energy dependence when compared to measurements at RHIC energies. This provides a new insight for understanding the nature of the charge-dependent azimuthal correlations observed at RHIC and LHC energies. DOI: 10.1103/PhysRevLett.110.012301
Keywords: FLOW; Physics